1991
DOI: 10.1016/0741-5214(91)90251-o
|View full text |Cite
|
Sign up to set email alerts
|

Leg ulcer etiology—A cross sectional population study

Abstract: Three hundred eighty-two patients with active leg ulcers were clinically examined after random selection out of a population of 827 patients identified within a previous cross-sectional population survey. Bidirectional Doppler ultrasonography was used for objective assessment of arterial and venom circulation. The purpose was to register causative factors and the etiologic spectrum. Venous insufficiency was present in 332 (72%) of 463 legs with active ulceration; deep insufficiency occurred in 176 (38%), and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
4
10

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(137 citation statements)
references
References 19 publications
2
121
4
10
Order By: Relevance
“…These results are similar to those published by Nelzen et al, 12 Philips et al, 2 Callam et al, 13 Douglas et al, 6 Nelzen et al, who found leg ulcers with a venous etiology in percentages ranging from 75 to 90% of cases. In addition to the venous category, these authors classified ulcers etiologically as arterial, neuropathic, or mixed.…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to those published by Nelzen et al, 12 Philips et al, 2 Callam et al, 13 Douglas et al, 6 Nelzen et al, who found leg ulcers with a venous etiology in percentages ranging from 75 to 90% of cases. In addition to the venous category, these authors classified ulcers etiologically as arterial, neuropathic, or mixed.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, in 40 patients diagnosed with chronic venous ulcers (CVU), the concomitant presence of peripheral arterial disease (PAD) was detected in 10 (25%) of them by means of ABI; this ratio was lower than that described by Nelzen (40%), 4 but higher than those reported by Anderson (24.5%), 12 Scriven (14%) 11 and Callam (21%). 13 Thus, it could be stated that the detection of concomitant chronic venous ulcers (CVU) and peripheral arterial disease (PAD) was frequent in the population studied.…”
Section: Resultscontrasting
confidence: 54%
“…2 Venous ulcers are the most common type and represent 80% of ulcers in lower limbs with an overall prevalence ranging between 0.06 and 3.6%. [3][4][5][6] The most common and important cause of ulcers in the lower limbs is chronic venous insufficiency, followed by arterial disease which represents 10 to 25% of all ulcers and may coexist with venous disease. [2][3][4] Most venous ulcers are treated with some type of compression (compressive bands/Unna boots); thus, if patients present any arterial insufficiency, this commonly used treatment will be of little benefit and may also delay the healing process of an ulcer and cause greater damage, such as more pronounced ischemia in the affected limb.…”
Section: Introductionmentioning
confidence: 99%
“…Severe manifestations and ulceration occur in 4% to 6% and 7% to 23%, respectively [7,8]. The prevalence of venous ulceration is at least 300 per 100000 and approximately 25% are due to DVT [9,10]. In the United States, skin changes and ulceration are present in 6 to 7 million and 400,000 to 500,000 people, respectively [11].…”
Section: Introductionmentioning
confidence: 99%